2010
DOI: 10.1351/pac-con-09-10-17
|View full text |Cite
|
Sign up to set email alerts
|

Gold-catalyzed synthesis of N,O-heterocycles

Abstract: The selective synthesis of oxazoles, alkylidene oxazoles, and 1,3-oxazines from N-propargyl carboxamides by choosing gold(III) or gold(I) catalysts and selecting terminal or internal alkynes as substrates is discussed. The mechanistic studies based on labeling experiments and intensive in situ NMR studies indicate an anti-oxyauration step and a protodeauration with retention of the sterical arrangement at the double bond. The synthetic scope for gold(I) catalysts is very broad, allowing selective conversions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 8 publications
(7 reference statements)
0
14
0
1
Order By: Relevance
“…The gold‐catalysed synthesis of heterocycles is a highly useful tool 4. In this area we have developed a simple synthesis of oxazoles5 and alkylideneoxazolines6 from N ‐propargylcarboxamides 7. The same class of substrates then also allowed the isolation of vinylgold intermediates,8 a technique which subsequently proved to be of broad scope 9…”
Section: Introductionmentioning
confidence: 99%
“…The gold‐catalysed synthesis of heterocycles is a highly useful tool 4. In this area we have developed a simple synthesis of oxazoles5 and alkylideneoxazolines6 from N ‐propargylcarboxamides 7. The same class of substrates then also allowed the isolation of vinylgold intermediates,8 a technique which subsequently proved to be of broad scope 9…”
Section: Introductionmentioning
confidence: 99%
“…This past decade has been the boom time for homogeneous gold catalysis, which was rather limited in organic synthesis until the advantages of gold complexes as catalysts were discovered [ 1 ]. In comparison to other transition-metal catalysts, most gold-catalyzed reactions are atom-economic, remarkably mild with regard to reaction conditions, and most importantly, have a different reaction scope [ 2 4 ].…”
Section: Reviewmentioning
confidence: 99%
“…One of the most important fundamental reactions in gold-catalyzed synthesis is the addition of X–H (X = O, N, C) bonds to C–C multiple bonds, which features diverse functional group tolerance and the easy formation of carbon–carbon and carbon–heteroatom bonds [ 1 , 4 5 ]. Furthermore, the rapid growing area of tandem reactions has allowed chemists to assemble diverse complex molecular frameworks more conveniently.…”
Section: Reviewmentioning
confidence: 99%
“…Gold(I) catalysis has been used to prepare N,O‐heterocycles by reaction of amides and hydroxylamine with alkynes and allenes and it is well recognized that electrophilic gold(I) catalysts are powerful mediators for the cycloisomerization of 1, n ‐enynes and their trapping with various nucleophiles . Although there is a wealth of work in this area, we identified that there were still untapped opportunities in the trapping of transient cyclopropyl‐gold(I) carbenes with oximes.…”
Section: Introductionmentioning
confidence: 98%